Considerations for Cultural and Social Spaces in University Library - Gazula, Suhasini (Developing Library Network, 2013)
This paper explores my thoughts on a research project, how social and cultural conditions play a major role in students’ life, and influences the social and cultural practices of the university library usage at Auckland University of Technology (AUT) Manukau Campus. This research will examine the students’ use of the library and the study space in and around the campus. This qualitative research is a case study to explore the library usage at the Manukau Campus. The exploration will be based on the interviews with my library colleagues and academic staff, including focus group methods with students, and observation of the influences on social and cultural practices on a university library usage at the Manukau Campus. The paper concludes that, while planning or redeveloping libraries, one needs to consider the social and cultural impact of spaces for students of different ethnicities and how these support peer learning, create a sense of belonging, encourage student retention, and contribute to increasing enrolment at the university.
Keywords: Family; Culture; Language; Pasifika; Social Space; Technology